Pilar-pilar Keunggulan Kompetitif: Sebuah Pandangan Berbasis Sumber Daya - Dede Hertina; Mohamad Bayu Herdiawan Hidayat (Universitas Muhammadiyah Sidoarjo, 2019)
This article describes the economic activities that underlie a resource-based view of competitive advantage and integrate existing perspectives into a model of saving from resources and company performance. The essence of this model are the four conditions that underlie sustainable competitive advantage, all of which must be met. These include superior resources (heterogeneity in an industry), ex post limits to competition, imperfections in resource mobility, and limits before competition (ex ante limits to competition). In the concluding section, application models are discussed both for single business strategies and corporate strategies.